Separation and recovery of iron and arsenic from acid leaching wastewater by valence state transformation. Issue 5 (October 2021) - Cao, Pan; Long, Hua; Zhang, Mengxin; Zheng, Yajie
Abstract: Acid leaching wastewater, produced in the acid pre-leaching process of gold-bearing dust, contains a lot of iron (Fe) and arsenic (As). If these wastewater are discharged directly without proper treatment, massive destruction on the environment will be caused, and a large amount of arsenic and iron resources will be wasted. In this study, Fe(III) reduction by pyrite, recovery and purification of crude green-vitriol and crude As2 O3, and disposal of arsenic-bearing solid waste were studied. Based on those studies, a novel process containing Fe(III) reduction with pyrite, iron recovery after Fe(III) reduction, and arsenic recovery from the solution after iron recovery was proposed to separate and recover Fe and As from an acid leaching wastewater. Results showed that reduction efficiency of Fe(III) in acid leaching wastewater achieved 96.43% under the optimal conditions (80 °C, L S −1 5:1, 3 h). Recovery efficiency of iron in crude green-vitriol achieved 82.37%; moreover, 73.32% As remained in the solution after iron recovery. Through purification, purified green-vitriol reached the national standard of class-I green-vitriol (GB 10531-2006), and the direct recovery efficiency of iron was 51.46%. Through neutralization, SO2 reduction, recovery and purification of crude As2 O3, purified As2 O3 reached the national standard of As2 O3 -3 (GB 26721-2011), and the direct recovery efficiency of arsenic achieved 74.89%. This process realized the efficient recovery of iron and arsenic from acid leaching wastewater, and also realized the harmless disposal of arsenic-containing solid waste. Graphical Abstract: ga1 Highlights: A novel process was proposed to separate and recover Fe and As from wastewater. The efficient separation and recovery of Fe and As was achieved. Purified green-vitriol reached the national standard of I product (GB 10531-2006). Purified As2 O3 reached the As2 O3 -3 product standard in GB 26721-2011. The direct recovery efficiency of Fe and As achieved 51.46% and 74.98%, respectively.